2012
DOI: 10.1002/bip.22145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amylose deposition on potato tuber starch granule architecture and dynamics as studied by lintnerization

Abstract: The effect of amylose deposition on the amylopectin crystalline lamellar organization in potato starch granules was studied by mild acid, so-called lintnerization, of potato tuber starch transgenically engineered to deposit different levels of amylose. The starch granules were subjected to lintnerization at different temperatures (25, 35, and 45°C) and to two levels of solubilization, ∼ 45 and 80%. The rate of the lintnerization increased with temperature but was suppressed by amylose. The molecular size of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 47 publications
5
28
0
Order By: Relevance
“…In amylose‐free and low‐amylose containing starches, the apparent annealing effect was more pronounced than in normal potato starch. All three starches had similar amylopectin structures and phosphate content, and it was thus concluded that it was the presence of amylose that retarded the effect . Interestingly, in an earlier work comparing amylose‐free maize (A‐type allomorph) and potato starches, it was found that the temperature had an effect on the composition of the lintnerized starch only in the potato sample .…”
Section: Introductionmentioning
confidence: 94%
“…In amylose‐free and low‐amylose containing starches, the apparent annealing effect was more pronounced than in normal potato starch. All three starches had similar amylopectin structures and phosphate content, and it was thus concluded that it was the presence of amylose that retarded the effect . Interestingly, in an earlier work comparing amylose‐free maize (A‐type allomorph) and potato starches, it was found that the temperature had an effect on the composition of the lintnerized starch only in the potato sample .…”
Section: Introductionmentioning
confidence: 94%
“…The "Maltese cross" also remains [48], which shows that the organized molecular segments are confined to the crystallites. The crystallites are formed by short, external chain segments of amylopectin with a degree of polymerization (DP) approximately 10-20 glucosyl units [49][50][51][52]. As two chains unite into a double-helix with 6 glucose residues per turn of each strand and a pitch of 2.1 nm [53], the length of these double-helices is about 4~6 nm.…”
Section: Crystallinitymentioning
confidence: 99%
“…Unlike amylose, however, there is great additional variation with respect to the unit chain lengths and branching patterns. Chain length, expressed in DP, is used to quantify the molecular weight In addition, each macromolecule contains a single C-chain which carries the sole reducing end group (Figure 1.3) (Wikman, Blennow & Bertoft, 2013). …”
Section: Composition Of Starch Granulesmentioning
confidence: 99%
“…The less dense amorphous shells contain amylose and less ordered amylopectin, whereas the semi-crystalline material consists of regular repeat of alternating amorphous and crystalline lamellae. At higher level organization, the semi-crystalline rings are associated with the amylopectin structures (Wikman, Blennow & Bertoft, 2013). The amylopectin molecule is highly branched with its side chain branches forming rigid double helices that associated into clusters (Figure 1.5).…”
Section: Granular Structurementioning
confidence: 99%
See 1 more Smart Citation